Industrial wastewater coagulation using ferrate derived from waste iron sludge - Reaño, Johanna Marie P. (2012)
Potassium ferrate (K2FeO4) synthesized from iron-containing drinking water treatment sludge was used in the treatment of semiconductor wastewater. The standard jar test apparatus was used in the study. Wet chemical oxidation method was done to synthesizer the ferrate from the iron-rich drinking water treatment sludge. Response surface methodology (RSM) particularly IV-Optimal statistical experiment design was used to investigate the effect of ferrate dosage and pH to residual turbidity and true color. The optimum condition to achieve minimum residual turbidity and residual true color was a ferrate dosage of 0.5 mg/L at pH 6, which is much lower than that of commercial FeCl3 and PAC with optimum dosages of 40 mg/L and 4 mg/L, respectively. The sludge derived ferrate achieved 98% in both turbidity and true color removals, which are comparable with commercial FeCl3 and PAC. Moreover,at this optimum condition of sludge-derived ferrate, 89% COD removal was achieved, which is higher than those achieved by FeCl3 and PAC at optimum conditions. After settling, sludge-derived ferrate exhibited the highest reduction in zeta potential from -52 mV to -12.12 mV as compared to FeCl and PAC which had a final zeta potential of -19.27 mV and -17.1 mV, respectively. This study proved that ferrate solution induced from wste drinking water treatment sludge can perform remarkably compared with commercial coagulants in terms of cost, zeta potential lowering, COD, turbidity, and true color removals of actual semiconductor wastewater.